Quantification of human lithostathine by high performance liquid chromatography. Issue 4 (April 1995) - Bernard, J P; Barthet, M; Gharib, B; Michel, R; Lilova, A; Sahel, J; Dagorn, J C; De Reggi, M
Abstract : Pancreatic stones of patients with chronic calcifying pancreatitis (CCP) are mostly made up of CaCO3 crystals. Formation and growth of such crystals is inhibited in vitro by lithostathine, a protein present in normal pancreatic juice. Decreased lithostathine activity was therefore suspected in patients with CCP, but comparison by immunoassay of lithostathine concentrations in the pancreatic juices of patients and controls led to conflicting results. This study shows that these discrepancies might have been caused in part by a remarkably high susceptibility of the protein to trypsin like cleavage, resulting in important structural changes and concomitant modifications of the epitopes. A novel lithostathine assay in juice was developed, based on separation of secretory proteins by high performance liquid chromatography. The chromatographic separation of lithostathine was based on hydrophobic interactions at pH 5.0 using a Phenyl-TSK column. This study showed with this assay that lithostathine concentrations (microgram/mg of total protein) were similar in CCP patients with alcoholic aetiology (mean (SD) 6.3 (2.7)) and other aetiologies (7.2 (3.7)), but one third of those estimated in patients without pancreatic disease (16.7 (4.3)). Similar concentrations were found, however, in chronic alcoholic patients without CCP (6.6 (3.3)) and in patients with CCP. It was concluded that decreased lithostathine concentration is associated with CCP, although such a decrease is not sufficient by itself for the disease to occur.